PELATIHAN DAN BUDAYA ORGANISASI TERHADAP KINERJA PADA PERAWAT RUMAH SAKIT PUPUK KALTIM DI BONTANG - Nurul Fatimah; Sukisno Selamet Riadi; Purwadi Purwadi (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2020)
Abstract - This study discusses the Training and Organizational Culture of the Performance of Nurses of PKT Hospitals in Bontang. This research is quantitative, the method used to collect data is a questionnaire. Respondents in this study were nurses in Bontang PKT Hospital precisely nurses who served in the Emergency Department, Hemodialysis, Outpatient Clinic Nurses, Obstetric and Gynecology Nurses, totaling 50 people. The analytical method used in this research is multiple linear regression analysis and path analysis through SPSS 22 software. The results of this study indicate that there is an influence of training and organizational culture on employee performance partially, there is the effect of training on performance and there is an influence of organizational culture on performance.